The Ultimate Terrorists - Stern, Jessica 1958- (London Harvard University Press, 2001)
As bad as they are, why aren't terrorists worse? With biological, chemical and nuclear weapons at hand, they easily could be. Jessica Stern argues that the nuclear threat of the Cold War has been replaced by the more imminent threat of terrorist attacks with weapons of mass destruction.
Include Notes and Index
Keywords: Terrorism -- Terrorism -- Technological innovations